2022
DOI: 10.46747/cfp.6808595
|View full text |Cite
|
Sign up to set email alerts
|

Mild asthma in adults and adolescents

Abstract: sthma is common in Canada, with a prevalence of 10.8%. 1 Unfortunately, asthma is poorly controlled in at least half of patients. 1 Since asthma is frequently encountered in primary care settings, family physicians are well positioned to optimize asthma management and improve outcomes.Recent years have seen the publication of new landmark asthma trials and updated Canadian asthma guidelines, as well as the regulatory approval of new asthma drug products and devices. This article highlights some relevant update… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Health systems and clinicians must continue to develop and implement patient-centered approaches to pain management for patients with established long-term opioid therapy . Clinically recommended approaches include discussing patients’ experiences with both positive and negative associations of long-term opioid therapy and other pain management strategies, developing risk reduction plans and addiction-informed treatment strategies for patients with signs of OUD, and facilitating voluntary opioid tapering for patients who are interested in lowering their dosages …”
Section: Discussionmentioning
confidence: 99%
“…Health systems and clinicians must continue to develop and implement patient-centered approaches to pain management for patients with established long-term opioid therapy . Clinically recommended approaches include discussing patients’ experiences with both positive and negative associations of long-term opioid therapy and other pain management strategies, developing risk reduction plans and addiction-informed treatment strategies for patients with signs of OUD, and facilitating voluntary opioid tapering for patients who are interested in lowering their dosages …”
Section: Discussionmentioning
confidence: 99%
“…35 If patients reveal a low readiness to taper, clinicians can respond using motivational interviewing techniques such as listening, asking, and informing to enable patients to identify barriers to change. 14,29 Motivational interviewing may also support patients along their tapering journey. A recent study found that patients with chronic pain who received weekly consultations with a physician assistant to discuss barriers and motivations for tapering (in addition to pain self-management strategies) were able to achieve lower daily doses of opioids without increased pain.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also received an educational DVD, relaxation CD, mindfulness CD, and distraction techniques. Additionally, participants had an individual, 1-hour consultation (based on motivational interviewing) with a nurse, 2 monitoring telephone calls (30 minutes each), and a face-to-face consultation (1 hour) . Nurses used a tapering app specifically designed for this trial that computed a standard opioid tapering plan consisting of a reduction of 10% of the baseline dose each week until 30% of the baseline dose was reached, then a reduction of 10% of the remaining dose per week (eTable 3 in Supplement 2).…”
Section: Methodsmentioning
confidence: 99%
“…Case studies illustrating successful opioid tapering and challenges were discussed. Participants also received an educational DVD, 12 Nurses used a tapering app specifically designed for this trial that computed a standard opioid tapering plan consisting of a reduction of 10% of the baseline dose each week until 30% of the baseline dose was reached, then a reduction of 10% of the remaining dose per week (eTable 3 in Supplement 2). The tapering program was individualized according to opioid preparation and individual circumstances.…”
Section: Key Pointsmentioning
confidence: 99%